2008
DOI: 10.1063/1.3005884
|View full text |Cite
|
Sign up to set email alerts
|

Interface and bulk magnetization dynamics in biaxial Fe/Cr structures induced by ultrashort optical pulses

Abstract: The interface and bulk magnetization dynamics of single-crystalline, wedge-shaped Fe͑001͒ thin films with Cr cap layers have been studied by time-resolved magneto-optical Kerr effect ͑MOKE͒ and time-resolved magnetization-induced second harmonic generation ͑MSHG͒ using an all-optical pump-probe technique. We observed long-lived ͑Ϸ1 ns͒ MOKE and MSHG oscillations excited by ultrashort ͑Ϸ150 fs͒ optical pulses. They exhibit the same main resonance frequency f and damping constant. However, a 90°phase shift was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that the damping of precessional dynamics in ferromagnetic metals can be complicated by the action of many extrinsic damping processes such as inhomogeneous broadening, 15 two-magnon scattering, [16][17][18] interface effects, 19 and spin diffusion into adjacent metallic layers, 14,15,20 with Cr in particular shown to be a strong spin scatterer. 21 Müller et al observed a sharp increase in the damping in CrO 2 films above a threshold pump fluence, possibly due to spin-wave instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the damping of precessional dynamics in ferromagnetic metals can be complicated by the action of many extrinsic damping processes such as inhomogeneous broadening, 15 two-magnon scattering, [16][17][18] interface effects, 19 and spin diffusion into adjacent metallic layers, 14,15,20 with Cr in particular shown to be a strong spin scatterer. 21 Müller et al observed a sharp increase in the damping in CrO 2 films above a threshold pump fluence, possibly due to spin-wave instabilities.…”
Section: Introductionmentioning
confidence: 99%